2018
DOI: 10.1039/c8tc03696a
|View full text |Cite
|
Sign up to set email alerts
|

A simple strategy to achieve remarkable mechanochromism of cationic Ir(iii) phosphors through subtle ligand modification

Abstract: Herein, a facile and feasible strategy to control the mechanochromism of Ir(iii) complexes through simple adjustment of the dipole moment is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…[23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The former one is attributed to the π‐π* transitions delocalized along the π‐electronic system. The latter one is assigned to an intramolecular charge transfer (ICT) transition from triphenylamine unit to benzothiazole group [10] . Increasing solvent polarity, the absorption of P1 is not dramatically changed, but the emission color exhibits an obvious red‐shifted from blue (in n‐Hexane λ em =441 nm) to yellow (in dimethylformamide λ em =524 nm) (Figure 1b, 1c, and S1).…”
Section: Resultsmentioning
confidence: 99%
“…453 Since then, various mono-and dinuclear Ir(III) complexes with MCL have been developed. 50,109,110,463,[486][487][488][489][490][491][492][493] Interestingly, in most of the cases, AIE and MCL activity are observed simultaneously. This is consistent with the opinion first expressed by Chi"s group, that AIE materials may be a key treasure source for mechanochromic luminescence.…”
Section: Ir(iii) Complexesmentioning
confidence: 98%
“…This is consistent with the opinion first expressed by Chi"s group, that AIE materials may be a key treasure source for mechanochromic luminescence. 445 There are four different types of MCL Ir(III) complexes based on the structure of the ancillary ligand, including alkyl chains, [486][487][488][489][490][491] dendrimer-like, 492 Schiff base 50,109,110 and rigid aromatic ring. 463,493 Fig.…”
Section: Ir(iii) Complexesmentioning
confidence: 99%